Pengaruh Perubahan Undang-Undang Pajak Penghasilan Tahun 2008 terhadap Harga Saham dan Kebijakan Dividen - Amiruddin, Zaenal Arifin (Sinergi: Kajian Bisnis dan Manajemen, 2012)
This research examines the effects of changes in income tax law in 2008 to the stock price and dividend policy. The law reduces the maximum boundaries of income taxe rate and devidend tax rate as well. The results show that investors respond positively to the announcement of changes in the tax rate on the date of the announcement and no information was leaked before the announcement. But investor reaction to the announcement somewhat exaggerated due to rising prices keep going until a few days later followed by a decline. There is a phenomenon of overreaction in the incident. This research also found that tax changes affect corporate dividend policy. The Company will pay a larger portion of dividends by the reduced tax rate.Keywords: The announcement of income tax law 2008, tax rate, stock price, dividend payout ratio